Evaluation of the Effects of Electrical and Carbon Dioxide Stunning Methods on Quality Attributes of Pork Meat - Gábor Jónás; Anna Visy; István Dalmadi; Koppány Majzinger; Nóra Krzyzewsky; Annamária Barkó; József Surányi; László Friedrich (Applied Sciences)
In our experiment, the effect of electrical and CO2 stunning on pork meat quality attributes was studied. A total of thirty PIC337 female pigs were allocated to two equal groups which were stunned electrically (50 Hz, 210 V, 2.6 A, 15 s) or by CO2 (85 V% CO2, 15 V% O2, 90 s) and slaughtered at a commercial slaughterhouse. For 24 h post mortem, the carcass m. gluteus medius (GM) was used to evaluate meat quality attributes such as pH, color, hardness, water holding capacity (WHC), and total pigment content, and meat classification was also carried out. The CO2 stunning resulted in muscle with significantly lower pH (p < 0.01) and poorer water holding capacity (p < 0.05) compared to electrical stunning. The GM of pigs stunned electrically showed significantly increased lightness (L*) and redness (a*) (p < 0.05) compared to CO2-stunned. The time course of development of rigor mortis was similar for both stunning methods. Pale, soft, exudative (PSE) or dark, firm, dry (DFD) meat defects were not observed. Based on total pigment content, stunning methods did not significantly affect the amount of removable blood.